Frog, where are you? - Mayer, Mercer, 1943- (New York : Dial Books for Young Readers, 1969)
A boy and his dog suffer through several adventures while searching for a pet frog that escaped during the night.
Sequel to: A boy, a dog, and a frog.
Keywords: Frogs -- Fiction; Stories without words